Thonningianin A ameliorates acetaminophen-induced liver injury by activating GPX4 and modulating endoplasmic reticulum stress - Lai, Shanglei; Ye, Yingyan; Ding, Qinchao; Hu, Xiaokai; Fu, Ai; Wu, Lan; Cao, Wenjing; Liu, Qingsheng; Dou, Xiaobing; Qi, Xuchen (Frontiers in Pharmacology, 2025)
IntroductionAcetaminophen (APAP) is widely used as an analgesic and antipyretic. However overdose APAP can lead to acute liver injury (ALI), representing a significant challenge for public health due to limited treatment options. Current research highlights the need for safer and more effective therapies for APAP-induced liver injury, especially those that target oxidative and endoplasmic reticulum (ER) stress pathways. This study investigates the protective effects of Thonningianin A (TA), a flavonoid compound derived from Penthorum chinense Pursh, in mitigating APAP-induced hepatotoxicity.MethodsThe experimental design involved administering TA at doses of 20 mg/kg and 40 mg/kg to C57BL/6 mice prior to inducing hepatotoxicity with APAP.Results and discussionTA treatment significantly lowered plasma ALT and AST levels, inhibited the production of inflammatory cytokines, and reduced oxidative stress markers in liver tissues. Furthermore, TA modulated apoptosis-related proteins by increasing BCL-2 expression while decreasing CHOP and BAX levels. It alleviated endoplasmic reticulum (ER) stress by downregulating GRP78, p-PERK, and ATF4. Notably, liver-specific GPX4 knockdown, achieved through AAV-8-mediated shRNA delivery, abolished the hepatoprotective effects of TA, underscoring GPX4’s essential role in mediating TA-induced hepatoprotection. These findings suggest TA as a promising therapeutic agent in managing APAP-induced liver injury, with its unique action on both oxidative and ER stress pathways contributing to its hepatoprotective efficacy.